2014
DOI: 10.3892/ijo.2014.2505
|View full text |Cite
|
Sign up to set email alerts
|

NVP-BEZ235, a dual PI3K/mTOR inhibitor synergistically potentiates the antitumor effects of cisplatin in bladder cancer cells

Abstract: The PI3K/Akt/mTOR pathway is a prototypic survival pathway and constitutively activated in many malignant conditions. Moreover, activation of the PI3K/Akt/mTOR pathway confers resistance to various cancer therapies and is often associated with a poor prognosis. In this study, we explored the antitumor effect of NVP-BEZ235, a dual PI3K/mTOR inhibitor in cisplatin-resistant human bladder cancer cells and its synergistic interaction with cisplatin. A human bladder cancer cell line with cisplatin resistance was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 38 publications
(31 reference statements)
2
44
1
Order By: Relevance
“…31 Indeed, protein synthesis, which is required for cell growth and cell cycle progression, is regulated by mTORC1, while PI3K-Akt as well as mTORC2 activation is also important for cell survival. 32,33 Interestingly, in consistent with recent studies, 34,35 we found that NVP-BEZ235 caused increased phosphorylation of MEK/Erk, although it appeared to be less significant compared with mTOR or PI3K inhibitors. 34,35 It has been suggested that activation of MEK/Erk signaling is a resistance mechanism in mTOR inhibitor-based therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…31 Indeed, protein synthesis, which is required for cell growth and cell cycle progression, is regulated by mTORC1, while PI3K-Akt as well as mTORC2 activation is also important for cell survival. 32,33 Interestingly, in consistent with recent studies, 34,35 we found that NVP-BEZ235 caused increased phosphorylation of MEK/Erk, although it appeared to be less significant compared with mTOR or PI3K inhibitors. 34,35 It has been suggested that activation of MEK/Erk signaling is a resistance mechanism in mTOR inhibitor-based therapy.…”
Section: Discussionsupporting
confidence: 90%
“…32,33 Interestingly, in consistent with recent studies, 34,35 we found that NVP-BEZ235 caused increased phosphorylation of MEK/Erk, although it appeared to be less significant compared with mTOR or PI3K inhibitors. 34,35 It has been suggested that activation of MEK/Erk signaling is a resistance mechanism in mTOR inhibitor-based therapy. Consequently MAPK/Erk inhibitors can improve antitumor effect of PI3K-mTOR inhibitors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In order to overcome chemotherapy resistance, BEZ235 had been developed and showed effective inhibition on cell growth of various cancers in the presence of cisplatin resistance. 26,27 In conclusion, this study demonstrated that tunicamycin could stimulate ERS and downregulate relevant proteins of the PI3K/AKT/mTOR signaling pathway in time-and dose-dependent manners and that ERS increased autophagy and apoptosis of MCF-7 cells as well as chemosensitivity of MCF-7 cells to cisplatin through inhibition of the PI3K/ AKT/mTOR signaling pathway. Nevertheless, the relationship between ERS and MCF-7 cells has not been clearly explained.…”
Section: Discussionmentioning
confidence: 60%
“…The ERK pathway parallels the PI3K/mTOR pathway, which is important in cardiomyocyte survival during stress (Das et al, 2009). ERK signaling is enhanced after treatment with BEZ (Moon et al, 2014), which essentially redirects signaling away from PI3K into RAS, leading to cardiomyocyte survival. In addition, inhibition of mTORC1 with rapamycin protects the heart against ischemia-reperfusion injury through activation of JAK2/STAT3 (Das et al, 2012).…”
Section: Discussionmentioning
confidence: 99%